Risk factors and clinical outcomes in chronic coronary and peripheral artery disease: An analysis of the randomized, double-blind COMPASS trial. (February 2020) - Vanassche, Thomas; Verhamme, Peter; Anand, Sonia S; Shestakovska, Olga; Fox, Keith AA; Bhatt, Deepak L; Avezum, Alvaro; Alings, Marco; Aboyans, Victor; Maggioni, Aldo P; Widimsky, Petr; Berkowitz, Scott D; et al.
Aims: Secondary prevention in patients with coronary artery disease and peripheral artery disease involves antithrombotic therapy and optimal control of cardiovascular risk factors. In the Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) study, adding low-dose rivaroxaban on top of aspirin lowered cardiovascular events, but there is limited data about risk factor control in secondary prevention. We studied the association between risk factor status and outcomes, and the impact of risk factor status on the treatment effect of rivaroxaban, in a large contemporary population of patients with coronary artery disease or peripheral artery disease. Methods and results: We reported ischemic events (cardiovascular death, stroke, or myocardial infarction) in participants from the randomized, double-blind COMPASS study by individual risk factor (blood pressure, smoking status, cholesterol level, presence of diabetes, body mass index, and level of physical activity), and by number of risk factors. We compared rates and hazard ratios of patients treated with rivaroxaban plus aspirin vs aspirin alone within each risk factor category and tested for interaction between risk factor status and antithrombotic regimen. Complete baseline risk factor status was available in 27, 117 (99%) patients. Status and number of risk factors were both associated with increased risk of ischemic events. Rates of ischemic events (hazard ratio 2.2; 95% confidence interval 1.8–2.6) and cardiovascular death (hazard ratio 2.0; 1.5–2.7) were more than twofold higher in patients with 4–6 compared with 0–1 risk factors ( p < 0.0001 for both). Rivaroxaban reduced event rates independently of the number of risk factors ( p interaction 0.93), with the largest absolute benefit in patients with the highest number of risk factors. Conclusion: More favorable risk factor status and low-dose rivaroxaban were independently associated with lower risk of cardiovascular events.